A Narrative Review on Colorectal Adenocarcinoma in East Africa - Wismayer, Richard (Highlights on Medicine and Medical Research Vol. 1, 2021)
Colorectal cancer is the fourth leading cause of cancer death in the world. It is the third most commonly diagnosed malignancy in the world and is responsible for 1.4 million new cases and approximately 700,000 deaths in the year 2012. This paper is a review of work done on colorectal adenocarcinoma in East Africa showing geographic spread, age and sex ratios, clinical presentation, management and predominant histopathology. A steady increased incidence of CRC in East African countries is currently being documented however this is associated with a higher CRC-associated morbidity and mortality. Whilst the male: Female ratio varies between 1.2:1 to 1.88:1, up to 38% of CRC diagnosis are in patients younger than 40 years, in contrast to only 1.9% of CRC patients in Western developed countries such as the USA. Generally rectal carcinoma is more common than colon carcinoma and abdomino-perineal resections are commonly performed in up to between 54% - 71% due to the advanced stage of presentation of rectal tumours in East Africa. The late stage presentation and delayed effective treatment in East Africa may result in a higher morbidity in CRC patients. Interestingly there is a significant incidence of mucinous adenocarcinoma sub-groups compared to Western developed countries which carry a poor prognosis. A significant proportion of CRC patients have been found to have histological and demographic features which suggest that MSI-tumours and these tumours are more common in younger patients. However only a few authors have looked at the possibility of mismatch repair mutations in the genetic aetiopathogenesis of colorectal adenocarcinoma in East Africa. Colorectal cancer in East Africa requires more unravelling especially in the aetiopathogenesis and therefore immunohisto-chemical staining and MSI testing is being recommended to establish the molecular subtypes and hence the prevalence of Hereditary Non-Polyposis colorectal carcinoma (HNPCC). This will clarify the genetic aetiopathogenesis of colorectal adenocarcinoma in the East African region.